Bibliometric Analysis of Publications on Dental Caries and Dental Fluorosis from India - Rutuj Waghmare1 , Roshan Umate2 , Shobha Joshi3 , Manoj Patil4 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Introduction- Dentistry goes back to about 5000 BC when a “tooth worm” was believed to be the source ofdental caries. Repeated processes of acid generation lead to the superficial degradation of calcified tissue inthe tooth, and consequently cavitation. Work has shown that enamel demineralisation happens at a pH of 5.5and below. World Health Organization (WHO) mission is Health for all. Fluoride containing drinking waterand supplements such as tablets, gums, gel, and toothpastes are the major sources that could be responsiblefor increased fluoride consumption.At various periods of tooth growth, the ingestion of unnecessary fluoridemay have a number of consequences on teeth, including the presence of white lines or streaks on enamel,yellow or brown streaks on enamel, and the general participation of enamel with white or dark chalky stains.Material and method- A systematic Search Strategy was framed using the specific keywords related toDental Caries and Dental Fluorosis. The Web of Science Database was accessed and Search Query wasinput as “KP= (“Dental Caries*” OR “dental fluorosis*” OR “school children 8-13 Years*” OR DMFT* OR“Dean’s fluorosis Index*”)”.Result- Search output generated total 210 documents from 111 Sources (Journals, Books, etc.)Over theperiod from 1999 – 2020. Total Author’s Keywords (DE) were 664Conclusion- Dental caries is genuinely a neurological disease whose nature primarily depends on theexistence of fermentable sugar, host factors, cariogenic microbial flora and other related environmentalconditions. Researchers have proposed numerous theories within the context of dental caries. Fluoride isamong the relatively few contaminants that may cause significant public safety impacts in drinking water.Various types of exposure to fluoride have been found to influence systemic F material, thereby raising thelikelihood of fluoride sensitive diseases.